DYNAMICS OF CAST BASED DEPRIVATION IN CHILD UNDER NUTRITION IN INDIA - Rudra Narayan Mishra (Centre for Development Studies-WP380, 2006)
Nutritional deprivation among Indian children is one of the parameters of underdevelopment mentioned in development discourse in recent times. And such deprivation is more often associated with well known socio-economic indicators of deprivation; prominent among them is caste, which ranks the society into a hierarchy in terms of benefit and welfare. Though caste dimension has been frequently considered as a category of understanding deprivation, it is rare to find explicit disadvantage of caste in what is said as transforming capabilities into functioning. While caste disadvantage in any outcome shows a systematic pattern, it is never made clear as to what is the dynamics of this disadvantage in terms of characteristics bearing an association with a given outcome. This paper makes an attempt in illustrating the dynamics of caste-based deprivation considering the case of child under-nutrition. It essentially demonstrates the patterns of differentials in nutrition according to other potential correlates of under-nutrition within SC/ST and others and comments on the limits of translating a given set of capabilities in to functioning/outcome (child nutrition here). It finds that while deprivation gap according to potential correlates is higher in general compared with SC/STs, there is clear demonstration of differential translation of capabilities like education, residential status, work status into outcome like nutrition among the SC/STs vis--vis the others. The results are also confirmed with application of a logit model. The study uses the data from National Family Health Survey report (NFHS-2, 1998-99) for the purpose of this illustration.